Analisis Harga Pokok Penjualan Pada Laba Di Apotik Kimia Farma No. 66 Luwuk - Siswadi Sululing; Doddy Asharudin (Jurnal Ekonomi, 2016)
This study entitled " Analysis of Cost of Goods Sold In Profit In Kimia Farma Pharmacy 66 Luwuk, with the formulation of the problem is: " Is the Price Determination of Sales At Kimia Farma No. 66 Luwuk Has Earned Income Optimal? "This study aims to determine the Price Determination of Sales and Profits What is optimal at Kimia Farma Pharmacy 66 Luwuk using Descriptive Analysis. The results showed that the calculation of the cost of goods sold from 2013 through 2014 can be seen Profits are not yet optimal because the sales targets set each year has not been reached. Profit decline that occurs due to declining prescription sales of credit and operational costs which did not experience significant differences.